Family Place Libraries™ - Gouzie, Deanna (Maine Policy Review, 2013)
This article discusses Family Place Libraries™ which are part of a national initiative that has redefined library service to children by expanding the traditional role of the library and recognizing that libraries play a crucial role in helping to build healthy families and community.
Keywords: Maine; libraries; Family Place libraries™